Mobile application for food donation - Yue, Yizhe (Nanyang Technological University, 2022)
Food waste had became one of the serious waste stream in Singapore . This project is going to design an mobile application that can provide a platform for Singaporean to donate their excess food through the application , in order to reduce the food waste in Singapore.